Website e-Commerce Penjualan Sepatu Sekolah Studi Kasus : Toko Sepatu Nadin di Tembilahan - Dwi Yuli Prasetyo (Program Studi Teknik Industri, 2020)
The rapid development of technology makes users increasingly spoiled by their presence, especially those that are developing today, namely e-commerce websites, especially with the spread of the Covid-19 virus pandemic that occurs almost everywhere around the world, making people very afraid to interact outside the home, with e-commerce makes buyers or consumers very easy in the process of purchasing transactions. Consumers do not need to come to the Nadin Tembilahan shoe store but they only need to open an e-commerce website using either a handphone or a computer, buyers can choose and buy the desired shoes. Nadin shop is one of the shops that operates in the shoe sales department in the area of tembilahan, managing a shoe shop is not as easy as imagined. Lack of sales in the days of the Covid-19 pendemic and the difficulty of processing payments and shipping goods, making a decrease in sales turnover shoes. Another problem faced by Nadin shoe stores is one of them is the process of selling shoes that still use the manual system, not yet done using e-commerce websites. Many weaknesses and omissions such as slow sales services, stacking shoes, inaccurate and timely reporting. With this problem the researchers tried to help to design a shoe sales e-commerce website, with the presence of this e-commerce very helpful for shop owners in managing their shoe stores, this proved to easily convey the promotion of shoes to the public, purchase transactions, payment and shipping of goods, because the buyer does not have to come to the shop, the buyer just simply makes a purchase transaction and waits for his shoes to come home. The presence of this e-commerce website really helped Nadin shopkeepers in Tembilahan in running their business and also provided a decent profit especially during the Covid-19 virus pandemic.